Spermatophore development in drones indicates the metabolite support for sperm storage in honey bees (Apis cerana) - Yan, Lele; Song, Huali; Tang, Xiangyou; Peng, Xiaomei; Li, Yaohui; Yang, Huan; Zhou, Zeyang; Xu, Jinshan (Frontiers in Physiology, 2023)
Developing effective long-term sperm storage strategies to maintain activity requires an understanding of the underlying spermatophore developmental phase in drones. Here we compared the developmental processes and metabolites about seminal vesicles of drones from different parentages(0-24d)in honeybee colonies, including mated queens, virgin queens, and worker bees. The results showed a similar developmental trend of seminal vesicles in the three drones on the whole, although there were significant differences in developmental levels, as well as in other indicators. Correlation analysis showed significant positive correlations between seminal vesicle width and sperm viability. The metabolomics of the seminal vesicles in drones from mated queens showed differences of the metabolites in each stage. Particularly, squalene identified among them was validated a protective effect on sperm vitality in vitro experiments. Together the results of these assays support that there were significant differences in the developmental levels of seminal vesicles among the three drones in honeybees, wherein a significant correlation between sperm viability and the developmental levels of seminal vesicles were dissected. The metabolomics analysis and semen storage experiments in vitro display signatures of squalene that may act as an effective protective agent in maintaining sperm viability. Collectively, our findings indicate that spermatophore development in drones provides metabolite support, which contributes to research on the differences of sperm viability among drones in the future.